A method for preparing an environmentally friendly plastic bag

By modifying silica nanoparticles and combining them with PLLA and PBAT using a specific reaction process, the method addresses the incompatibility issues, improving the mechanical and barrier properties of the composite material for packaging applications.

CN118931138BActive Publication Date: 2024-12-13ANHUI HENGGUAN PACKAGING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411428408.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-13
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The incompatibility between poly-L-lactic acid (PLLA) and polybutylene adipate/terephthalate (PBAT) leads to unsatisfactory mechanical properties, oxygen barrier properties, and water vapor barrier properties in composite polymer materials, limiting their application as packaging materials.

Method used

A method involving the modification of silica nanoparticles with hydroxymethyltrimethylsilane, followed by reactions with D-lactic acid and p-toluenesulfonic acid to create end-capped PDLA-linked silica, which is then combined with PLLA, PBAT, and epoxidized soybean oil to form a composite material using a twin-screw extruder and film-blowing process.

Benefits of technology

The method enhances the mechanical properties, oxygen barrier properties, and water vapor barrier properties of the plastic bag, ensuring stability and safety in food packaging while maintaining flexibility and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of plastic technology, and in particular to a method for preparing an environmentally friendly plastic bag. The present invention uses silicon dioxide grafted with end-capped PDLA chains, epoxy soybean oil, PLLA, and PBAT to prepare an environmentally friendly plastic bag by blending, extruding, and blowing films. The introduction of silicon dioxide grafted with end-capped PDLA chains not only enhances the mechanical properties of the plastic bag, but also improves its barrier properties, and effectively reduces the oxygen and water vapor permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, and in particular to a method for preparing an environmentally friendly plastic bag. Background Art

[0002] The development of social economy has promoted the rapid development of material packaging field. Most packaging materials are petroleum-based polymers, which are non-biodegradable.

[0003] PDLA (poly-D-lactic acid) and PLLA (poly-L-lactic acid) are two common polylactic acid (PLA) isomers, both of which are biodegradable polymer materials. Among them, poly-L-lactic acid (PLLA) is a promising substitute for petroleum-based polymers. PLLA comes from renewable resources and can help save energy. It is one of the most commercially valuable bio-based degradable polymers. In addition to good biodegradability and renewability, PLLA also has the characteristics of high mechanical strength, high optical transparency, high gloss, and excellent processing performance. However, the rigidity and brittleness caused by the high Tg of PLLA greatly limit its application as a packaging material. Polybutylene adipate / terephthalate (PBAT) has the characteristics of high flexibility, high elongation at break, and low tensile strength. Blending PBAT and PLLA can achieve complementary performance between the two. Therefore, blending PLLA and PBAT to obtain a composite polymer material with excellent performance is the most economical and effective solution. However, their incompatibility will lead to unsatisfactory mechanical properties of the blend, and poor oxygen barrier properties and water vapor barrier properties. Summary of the invention

[0004] In view of this, the purpose of the present invention is to propose a method for preparing an environmentally friendly plastic bag to solve the incompatibility problem between PLLA and PBAT and to improve the mechanical properties, oxygen barrier properties and water vapor barrier properties of the plastic bag prepared therefrom.

[0005] Based on the above purpose, the present invention provides a method for preparing an environmentally friendly plastic bag, comprising the following steps:

[0006] (1) Modifying silica nanoparticles with hydroxymethyltrimethylsilane to obtain hydroxymethylated silica;

[0007] (2) adding hydroxymethylated silica, D-lactic acid and p-toluenesulfonic acid to cyclohexane, heating to 110-130° C., reflux reaction for 8-12 hours, and after the reaction is completed, purifying to obtain PDLA chain grafted silica;

[0008] (3) adding PDLA-linked silica, 2-ethylhexanoic acid and p-toluenesulfonic acid to cyclohexane, heating to 170-190° C., and reflux reaction for 4-6 hours. After the reaction is completed, purifying to obtain end-capped PDLA-linked silica;

[0009] (4) PLLA, PBAT, silica grafted with end-capped PDLA chains, epoxy soybean oil and antioxidant are placed in a stirring pot and stirred evenly, and then melt-blended and extruded into granules using a twin-screw extruder, and then film-blown to obtain an environmentally friendly plastic bag.

[0010] Preferably, the average particle size of the silicon dioxide nanoparticles in step (1) is 100-300 nm.

[0011] Preferably, in step (1), the weight ratio of hydroxymethyltrimethylsilane to silicon dioxide nanoparticles is 10:0.08-0.12.

[0012] Furthermore, in the step (2), the weight ratio of hydroxymethylated silica to D-lactic acid is 10:28-41.

[0013] Preferably, the catalyst in step (2) is p-toluenesulfonic acid, and the added amount is 1%-3% of the weight of D-lactic acid.

[0014] Furthermore, in step (3), the weight ratio of silica grafted with PDLA chain to 2-ethylhexanoic acid is 10:1.1-1.7.

[0015] Preferably, the catalyst in step (3) is p-toluenesulfonic acid, and the added amount is 1%-3% of the weight of 2-ethylhexanoic acid.

[0016] Furthermore, in step (4), the amount of silica added to the end-capped PDLA chain grafts is 8%-12% of the total weight of PLLA and PBAT.

[0017] Furthermore, in step (4), the amount of epoxidized soybean oil added is 4%-6% of the total weight of PLLA and PBAT.

[0018] Preferably, the weight average molecular weight of PLLA in step (4) is 1×10 5 -1.5×10 5 The weight average molecular weight of PBAT is 0.8×10 5 -1.2×10 5 .

[0019] Preferably, the weight average molecular weight of the epoxidized soybean oil in step (4) is 900-1100.

[0020] Preferably, in step (4), the weight ratio of PLLA to PBAT is 65:35.

[0021] Preferably, the thickness of the environmentally friendly plastic bag in step (4) is 80±0.5 μm.

[0022] Beneficial effects of the present invention:

[0023] The environment-friendly plastic bag provided by the present invention is obtained by blending, extruding and blowing films using silica grafted with end-blocked PDLA chains, epoxy soybean oil, PLLA and PBAT, wherein the end-blocked PDLA chains in the silica grafted with the end-blocked PDLA chains can form a stereocomplex with PLLA, the epoxy soybean oil can react and increase the volume with PLLA and PBAT, and the silica in the silica grafted with the end-blocked PDLA chains can have a reinforcing effect on the PLLA and PBAT matrices, and the silica grafted with the end-blocked PDLA chains and the epoxy soybean oil synergistically achieve a balance between the flexibility and toughness of the plastic bag.

[0024] The silicon dioxide grafted with the end-capped PDLA chain provided by the present invention improves the oxygen barrier property and water vapor barrier property of the plastic bag. This is mainly because the end-capping of the PDLA chain improves the hydrophobicity on the one hand and reduces the channels for water molecule penetration on the other hand. In addition, the end-capped PDLA chain inhibits the migration of silicon dioxide in the plastic bag, so that the silicon dioxide is stably dispersed in the PLLA and PBAT matrices, thereby ensuring the safety and stability in food packaging.

[0025] The raw materials PLLA and PBAT of the environmentally friendly plastic bag provided by the present invention are both bio-based materials, have good biodegradability, can be gradually degraded in the natural environment, and reduce the environmental burden. The introduction of silicon dioxide grafted with the end-capped PDLA chain not only enhances the mechanical properties of the plastic bag, but also improves its barrier properties, effectively reduces the oxygen and water vapor permeability, prolongs the food shelf life, and reduces food waste. Epoxidized soybean oil, as a natural vegetable oil, improves the processing properties of the material and enhances the flexibility and durability of the plastic bag. DETAILED DESCRIPTION

[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0027] The average particle size of the silicon dioxide nanoparticles in the specific examples and comparative examples of the present invention is 200 nm, and the weight average molecular weight of PLLA is 1.35×10 5 The weight average molecular weight of PBAT is 1.08×10 5 The weight average molecular weight of epoxidized soybean oil is 950.

[0028] Embodiment 1:

[0029] (1) Dispersing 10 g of silica nanoparticles and 0.1 g of hydroxymethyltrimethylsilane in a mixed solution of 50 mL of ethanol and 200 mL of deionized water, heating to 60°C, stirring for 6 h, centrifuging, washing with ethanol three times, and drying at 80°C for 5 h to obtain hydroxymethylated silica;

[0030] (2) 10 g of hydroxymethylated silica, 34.57 g of D-lactic acid and 0.69 g of p-toluenesulfonic acid were added to 200 mL of cyclohexane, heated to 120 °C, and refluxed for 10 h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with deionized water for 3 times, then washed with methanol for 3 times, and finally dried at 80 °C for 6 h to obtain PDLA-linked silica.

[0031] (3) 10 g of PDLA chain grafted silica, 1.4 g of 2-ethylhexanoic acid and 0.028 g of p-toluenesulfonic acid were added to 200 mL of cyclohexane, the temperature was raised to 180°C, and the reaction was refluxed for 5 h. After the reaction was completed, the silica was cooled to room temperature, centrifuged, washed with deionized water for 3 times, and then washed with methanol for 3 times, and finally dried at 80°C for 6 h to obtain the end-capped PDLA chain grafted silica;

[0032] (4) 65 g of PLLA, 35 g of PBAT, 10 g of silica grafted with end-capped PDLA chains, 5 g of epoxidized soybean oil, and 0.58 g of antioxidant 168 were dried at 70°C for 6 h to remove moisture. The dried PLLA, PBAT, silica grafted with end-capped PDLA chains, and epoxidized soybean oil were then placed in a stirring pot and stirred evenly. The mixture was then melt-blended and extruded into granules using a twin-screw extruder, and film was blown to obtain an environmentally friendly plastic bag with a thickness of 80.2 μm.

[0033] Embodiment 2:

[0034] (1) Dispersing 10 g of silica nanoparticles and 0.08 g of hydroxymethyltrimethylsilane in a mixed solution of 50 mL of ethanol and 200 mL of deionized water, heating to 60 ° C, stirring for 6 h, centrifuging, washing with ethanol three times, and drying at 80 ° C for 5 h to obtain hydroxymethylated silica;

[0035] (2) 10 g of hydroxymethylated silica, 28 g of D-lactic acid and 0.28 g of p-toluenesulfonic acid were added to 200 mL of cyclohexane, heated to 110 °C, and refluxed for 12 h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with deionized water for 3 times, then washed with methanol for 3 times, and finally dried at 80 °C for 6 h to obtain PDLA-linked silica.

[0036] (3) 10 g of PDLA chain grafted silica, 1.1 g of 2-ethylhexanoic acid and 0.011 g of p-toluenesulfonic acid were added to 200 mL of cyclohexane, the temperature was raised to 170°C, and the reaction was refluxed for 6 h. After the reaction was completed, the silica was cooled to room temperature, centrifuged, washed with deionized water for 3 times, and then washed with methanol for 3 times, and finally dried at 80°C for 6 h to obtain the end-capped PDLA chain grafted silica;

[0037] (4) 65 g of PLLA, 35 g of PBAT, 8 g of silica grafted with end-capped PDLA chains, 4 g of epoxidized soybean oil, and 0.58 g of antioxidant 168 were dried at 70°C for 6 h to remove moisture. The dried PLLA, PBAT, silica grafted with end-capped PDLA chains, and epoxidized soybean oil were then placed in a stirring pot and stirred evenly. The mixture was then melt-blended and extruded into granules using a twin-screw extruder, and film was blown to obtain an environmentally friendly plastic bag with a thickness of 79.8 μm.

[0038] Embodiment 3:

[0039] (1) Dispersing 10 g of silica nanoparticles and 0.12 g of hydroxymethyltrimethylsilane in a mixed solution of 50 mL of ethanol and 200 mL of deionized water, heating to 60 ° C, stirring for 6 h, centrifuging, washing with ethanol three times, and drying at 80 ° C for 5 h to obtain hydroxymethylated silica;

[0040] (2) 10 g of hydroxymethylated silica, 41 g of D-lactic acid and 1.23 g of p-toluenesulfonic acid were added to 200 mL of cyclohexane, heated to 130 °C, and refluxed for 8 h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with deionized water for 3 times, then washed with methanol for 3 times, and finally dried at 80 °C for 6 h to obtain PDLA-linked silica.

[0041] (3) 10 g of PDLA chain grafted silica, 1.7 g of 2-ethylhexanoic acid and 0.051 g of p-toluenesulfonic acid were added to 200 mL of cyclohexane, the temperature was raised to 190°C, and the reaction was refluxed for 4 h. After the reaction was completed, the silica was cooled to room temperature, centrifuged, washed with deionized water for 3 times, and then washed with methanol for 3 times, and finally dried at 80°C for 6 h to obtain the PDLA chain grafted silica.

[0042] (4) 65 g of PLLA, 35 g of PBAT, 12 g of silica grafted with end-capped PDLA chains, 6 g of epoxidized soybean oil, and 0.58 g of antioxidant 168 were dried at 70°C for 6 h to remove moisture. The dried PLLA, PBAT, silica grafted with end-capped PDLA chains, and epoxidized soybean oil were then placed in a stirring pot and stirred evenly. The mixture was then melt-blended and extruded into granules using a twin-screw extruder, and film was blown to obtain an environmentally friendly plastic bag with a thickness of 80.3 μm.

[0043] Comparative Example 1:

[0044] The difference between Comparative Example 1 and Example 1 is that the silica grafted with the end-capped PDLA chains in step (4) is replaced with silica nanoparticles;

[0045] The specific preparation steps are as follows:

[0046] 65 g PLLA, 35 g PBAT, 10 g silica nanoparticles, 5 g epoxidized soybean oil, and 0.58 g antioxidant 168 were dried at 70 ° C for 6 h to remove moisture, and then the dried PLLA, PBAT, silica nanoparticles and epoxidized soybean oil were put into a stirring pot and stirred evenly, and then melt-blended and extruded into granules using a twin-screw extruder, and film blowing was performed to obtain an environmentally friendly plastic bag with a thickness of 80.1 μm.

[0047] Comparative Example 2:

[0048] The difference between Comparative Example 2 and Example 1 is that the silicon dioxide grafted with the end-capped PDLA chain in step (4) is replaced with silicon dioxide grafted with the PDLA chain;

[0049] The specific preparation steps are as follows:

[0050] (1) Dispersing 10 g of silica nanoparticles and 0.1 g of hydroxymethyltrimethylsilane in a mixed solution of 50 mL of ethanol and 200 mL of deionized water, heating to 60°C, stirring for 6 h, centrifuging, washing with ethanol three times, and drying at 80°C for 5 h to obtain hydroxymethylated silica;

[0051] (2) 10 g of hydroxymethylated silica, 34.57 g of D-lactic acid and 0.69 g of p-toluenesulfonic acid were added to 200 mL of cyclohexane, heated to 120 °C, and refluxed for 10 h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with deionized water for 3 times, then washed with methanol for 3 times, and finally dried at 80 °C for 6 h to obtain PDLA-linked silica.

[0052] (3) 65 g of PLLA, 35 g of PBAT, 10 g of PDLA-linked silica, 5 g of epoxidized soybean oil, and 0.58 g of antioxidant 168 were dried at 70 °C for 6 h to remove moisture. The dried PLLA, PBAT, PDLA-linked silica and epoxidized soybean oil were then placed in a stirring pot and stirred evenly. The mixture was then melt-blended and extruded into granules using a twin-screw extruder, and film was blown to obtain an environmentally friendly plastic bag with a thickness of 80.3 μm.

[0053] Comparative Example 3:

[0054] The difference between Comparative Example 3 and Example 1 is that the silica grafted with the end-capped PDLA chain in step (4) is replaced with PDLA;

[0055] The specific preparation steps are as follows:

[0056] (1) Add 34.57 g of D-lactic acid and 0.69 g of p-toluenesulfonic acid into 200 mL of cyclohexane, heat to 120 °C, and reflux for 10 h. After the reaction is completed, distill under reduced pressure, wash and dry to obtain PDLA;

[0057] (2) 65 g of PLLA, 35 g of PBAT, 10 g of PDLA, 5 g of epoxidized soybean oil, and 0.58 g of antioxidant 168 were dried at 70 °C for 6 h to remove moisture. The dried PLLA, PBAT, PDLA, and epoxidized soybean oil were then placed in a stirring pot and stirred evenly. The mixture was then melt-blended and extruded into granules using a twin-screw extruder, and film was blown to obtain an environmentally friendly plastic bag with a thickness of 80.2 μm.

[0058] Comparative Example 4:

[0059] Comparative Example 4 differs from Example 1 in that: no epoxy soybean oil is added;

[0060] The specific preparation is as follows:

[0061] (1) Dispersing 10 g of silica nanoparticles and 0.1 g of hydroxymethyltrimethylsilane in a mixed solution of 50 mL of ethanol and 200 mL of deionized water, heating to 60°C, stirring for 6 h, centrifuging, washing with ethanol three times, and drying at 80°C for 5 h to obtain hydroxymethylated silica;

[0062] (2) 10 g of hydroxymethylated silica, 34.57 g of D-lactic acid and 0.69 g of p-toluenesulfonic acid were added to 200 mL of cyclohexane, heated to 120 °C, and refluxed for 10 h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, washed with deionized water for 3 times, then washed with methanol for 3 times, and finally dried at 80 °C for 6 h to obtain PDLA-linked silica.

[0063] (3) 10 g of PDLA chain grafted silica, 1.4 g of 2-ethylhexanoic acid and 0.028 g of p-toluenesulfonic acid were added to 200 mL of cyclohexane, the temperature was raised to 180°C, and the reaction was refluxed for 5 h. After the reaction was completed, the silica was cooled to room temperature, centrifuged, washed with deionized water for 3 times, and then washed with methanol for 3 times, and finally dried at 80°C for 6 h to obtain the end-capped PDLA chain grafted silica;

[0064] (4) 65 g of PLLA, 35 g of PBAT, 10 g of silica grafted with end-capped PDLA chains, and 0.58 g of antioxidant 168 were dried at 70°C for 6 h to remove moisture. The dried PLLA, PBAT, and silica grafted with end-capped PDLA chains were then placed in a stirring pot and stirred evenly. The mixture was then melt-blended and extruded into granules using a twin-screw extruder, and film was blown to obtain an environmentally friendly plastic bag with a thickness of 80.1 μm.

[0065] Performance Test:

[0066] Mechanical properties: The mechanical properties of the plastic bag were tested using a tensile testing machine according to GB / T528-2009 standard. The test was carried out at room temperature with a tensile speed of 10 mm / min. The results are shown in Table 1.

[0067] Oxygen barrier properties: The test was conducted using an oxygen permeameter at room temperature with an O2 output pressure of 0.3 MPa. The results are shown in Table 1.

[0068] Water vapor barrier property: The water vapor permeability of the plastic bag was tested using a water vapor permeameter. The test temperature was room temperature and the relative humidity was 90%. The results are shown in Table 1.

[0069] Migration: Taking 4% acetic acid by volume as an acidic food simulant, the plastic bag was immersed in the acidic food simulant and the migration amount of silica after 60 days was tested. The results are shown in Table 1.

[0070] Table 1 Performance test results

[0071]

[0072] Data Analysis:

[0073] From the data of Examples 1-3 in Table 1, it can be seen that the environmentally friendly plastic bag prepared by the present invention has high tensile properties and elongation at break, indicating that it has excellent mechanical properties, and the oxygen permeability and water vapor permeability are both low, indicating that it has excellent oxygen and water vapor barrier properties. Although silicon dioxide is introduced into the raw materials for preparing the plastic bag of the present invention, its mobility in the acidic food simulant is low, indicating that it is firmly dispersed in the plastic bag film, thereby ensuring the safety and stability in food packaging.

[0074] It can be seen from the data of Example 1 and Comparative Example 1 in Table 1 that, relative to unmodified silica, the silica grafted with end-blocked PDLA chains prepared by the present invention improves the mechanical properties, oxygen barrier properties and water vapor barrier properties of the plastic bag. This is mainly because the silica grafted with end-blocked PDLA chains has good compatibility with PLLA and PBTA, and the silica grafted with end-blocked PDLA chains is uniformly and stably dispersed in the PLLA and PBTA matrices. In addition, the end-blocked PDLA chain grafts of silica effectively inhibit the migration of silica in the plastic bag in the acidic food simulant.

[0075] From the data of Example 1 and Comparative Example 2 in Table 1, it can be seen that the end-capping of the PDLA chain effectively improves the elongation at break of the plastic bag, while the tensile strength only shows a slight decrease, which indicates that the end-capping of the PDLA chain greatly improves the flexibility of the plastic bag while having little effect on the toughness. In addition, the end-capping of the PDLA chain significantly improves the water vapor barrier, which may be because the end-capping of the PDLA chain improves the hydrophobicity on the one hand and reduces the channels for water molecule penetration on the other hand.

[0076] It can be seen from the data of Example 1 and Comparative Example 3 in Table 1 that directly blending PDLA with PLLA and PBTA can effectively improve the elongation at break, but greatly reduce the tensile strength.

[0077] From the data of Example 1 and Comparative Example 4 in Table 1, it can be seen that the epoxy soybean oil and the silica grafted with the end-capped PDLA chain synergistically achieve a balance between the flexibility and toughness of the plastic bag, making it have high flexibility and high toughness at the same time. This is mainly due to the synergistic effect of the epoxy soybean oil reaction volume expansion effect, the end-capped PDLA chain stereocomplexation effect and the silica reinforcement effect.

[0078] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing an environmentally friendly plastic bag, characterized in that: The following steps are involved: (1) Modifying silica nanoparticles with hydroxymethyltrimethylsilane to obtain hydroxymethylated silica; (2) adding hydroxymethylated silica, D-lactic acid and p-toluenesulfonic acid to cyclohexane, heating to 110-130° C., reflux reaction for 8-12 hours, and after the reaction is completed, purifying to obtain PDLA chain grafted silica; (3) adding PDLA-linked silica, 2-ethylhexanoic acid and p-toluenesulfonic acid to cyclohexane, heating to 170-190° C., and reflux reaction for 4-6 hours. After the reaction is completed, purifying to obtain end-capped PDLA-linked silica; (4) PLLA, PBAT, silica grafted with end-capped PDLA chains, epoxy soybean oil and antioxidant are placed in a stirring pot and stirred evenly, and then melt-blended and extruded into granules using a twin-screw extruder, and film-blown to obtain an environmentally friendly plastic bag; In the step (2), the weight ratio of hydroxymethylated silica to D-lactic acid is 10:28-41; in the step (3), the weight ratio of silica grafted to the PDLA chain to 2-ethylhexanoic acid is 10:1.1-1.7; in the step (4), the amount of silica grafted to the end-capped PDLA chain is 8%-12% of the total weight of PLLA and PBAT, and the amount of epoxidized soybean oil is 4%-6% of the total weight of PLLA and PBAT.

2. The method for preparing an environmentally friendly plastic bag according to claim 1, characterized in that: The average particle size of the silicon dioxide nanoparticles in step (1) is 100-300 nm.

3. The method for preparing an environmentally friendly plastic bag according to claim 1, characterized in that: In the step (1), the weight ratio of hydroxymethyltrimethylsilane to silicon dioxide nanoparticles is 10:0.08-0.

12.

4. The method for preparing an environmentally friendly plastic bag according to claim 1, characterized in that: In the step (2), the amount of p-toluenesulfonic acid added is 1%-3% of the weight of D-lactic acid.

5. The method for preparing an environmentally friendly plastic bag according to claim 1, characterized in that: In the step (3), the amount of p-toluenesulfonic acid added is 1%-3% of the weight of 2-ethylhexanoic acid.

6. The method for preparing an environmentally friendly plastic bag according to claim 1, characterized in that: The weight average molecular weight of PLLA in step (4) is 1×10 5 -1.5×10 5 The weight average molecular weight of PBAT is 0.8×10 5 -1.2×10 5 .

7. The method for preparing an environmentally friendly plastic bag according to claim 1, characterized in that: The weight average molecular weight of the epoxidized soybean oil in step (4) is 900-1100.

8. The method for preparing an environmentally friendly plastic bag according to claim 1, characterized in that: The weight ratio of PLLA to PBAT in the step (4) is 65:

35.

9. The method for preparing an environmentally friendly plastic bag according to claim 1, characterized in that: The thickness of the environmentally friendly plastic bag in step (4) is 80±0.5 μm.

10. The method for preparing an environmentally friendly plastic bag according to claim 1, characterized in that: The antioxidant in step (4) is antioxidant 168.